Transitioning from crates to free farrowing: A roadmap to navigate key decisions - Baxter, Emma M.; Moustsen, Vivi A.; Goumon, Sébastien; Illmann, Gudrun; Edwards, Sandra A. (Frontiers in Veterinary Science, 2022)
There are animal welfare concerns about the continued use of permanent crating systems for farrowing and lactating sows, which is the most prevalent maternity system in global pig production. Greater societal attention in recent years has culminated in changes (or proposed changes) to regulations as well as market-driven initiatives to move away from crated systems. Transitioning from farrowing crates to systems that allow the sow greater freedom of movement and behavioural expression requires a number of key decisions, with various trade-offs apparent when trying to balance the needs of different stakeholders. This review discusses these decisions based on common questions asked by farmers, policy makers and other stakeholders when deciding on a new system to build/approve. Based on the latest scientific evidence and practical insight, decisions such as: whether to retrofit an existing barn or build a new one, what spatial dimensions are necessary per sow place, whether to adopt free farrowing or temporary crating, how to provide substrate/enrichment and be hygienic and environmentally friendly, and how to optimise the human inputs and transition between systems are considered. The aim of this paper is to provide a roadmap for those interested in uptake of higher welfare systems and practices, as well as to highlight areas requiring further optimisation and research.